2022
DOI: 10.3390/rs14102461
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Structure of Dust Aerosols Observed by a Ground-Based Raman Lidar with Polarization Capabilities in the Center of the Taklimakan Desert

Abstract: The vertical structure of dust properties in desert sources is crucial for evaluating their long-range transportation and radiative forcing. To investigate vertical profiles of dust optical properties in the Taklimakan Desert, we conducted ground-based polarization Raman lidar measurements in Tazhong (83.39°E, 38.58°N, 1103 m above sea level), located at the center of the Taklimakan Desert in the summer of 2019. The lidar system developed by Lanzhou University for continuous network observation is capable of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…The maximum value of AOD in the Taklimakan Desert was in April and the coarse-sized particles were the main component of aerosols in this region [61]. Zhang et al [62] found that the depolarization ratio of Taklimakan dust was 0.32 ± 0.06 at 532 nm, which did not change significantly compared with the depolarization ratio of dust aerosol transported to SACOL.…”
Section: Vertical Distribution Characteristics Of Aerosol In the Dust...mentioning
confidence: 96%
“…The maximum value of AOD in the Taklimakan Desert was in April and the coarse-sized particles were the main component of aerosols in this region [61]. Zhang et al [62] found that the depolarization ratio of Taklimakan dust was 0.32 ± 0.06 at 532 nm, which did not change significantly compared with the depolarization ratio of dust aerosol transported to SACOL.…”
Section: Vertical Distribution Characteristics Of Aerosol In the Dust...mentioning
confidence: 96%
“…The vertical structure plays a crucial role in facilitating the mixing of dust aerosols [21]. By using the ground-based polarization Raman lidar, Zhang et al [22] demonstrated that dust aerosols in the central Taklimakan Desert were regularly lifted over 6 km during the summer, while the majority of the dust remained restricted within 2 km. Based on the CALIPSO data analysis conducted in March 2021, Ye et al [23] revealed that the dust conveyance height was mostly concentrated at 1-3 km and 3-10 km.…”
Section: Introductionmentioning
confidence: 99%
“…The mineral dust that has been lifted in the air can, directly and indirectly, affect climate, which can in turn alter radiation balance in the atmosphere and act as cloud condensation nuclei to influence precipitation (Ginoux et al., 2001; Z. Huang et al., 2010; Zhang et al., 2022). Direct effect of dust aerosols on radiation balance (through absorption and scattering) influences the energy balance of the earth system (E‐cycle), while the organic matters carried by dust is associated with the carbon cycle (C‐cycle) (Dong et al., 2022; Z. Huang et al., 2022; J. Liu et al., 2022; Shao et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A typical dust devil can bring approximately 20 kg of dust into the atmosphere, while a very large one with a radius of over 100 m can carry about 15,000 kg of dust during its life span (Koch & Renno, 2005;Renno et al, 2004).The mineral dust that has been lifted in the air can, directly and indirectly, affect climate, which can in turn alter radiation balance in the atmosphere and act as cloud condensation nuclei to influence precipitation (Ginoux et al, 2001;Z. Huang et al, 2010;Zhang et al, 2022). Direct effect of dust aerosols on radiation balance (through absorption and scattering) influences the energy balance of the earth system (E-cycle), while the organic matters…”
mentioning
confidence: 99%